2007
DOI: 10.1128/jb.00703-07
|View full text |Cite
|
Sign up to set email alerts
|

Control of Methionine Synthesis and Uptake by MetR and Homocysteine in Streptococcus mutans

Abstract: thermophilus. These data suggest a common mechanism for the regulation of the methionine supply in streptococci. However, some streptococcal species are unable to synthesize the homocysteine coeffector. This intriguing feature is discussed in the light of comparative genomics and streptococcal ecology.The sulfur-containing amino acid methionine is of major importance in the cellular metabolism of all living organisms. Methionine is the universal initiator of protein synthesis, and its derivative S-adenosylmeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
76
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(83 citation statements)
references
References 45 publications
(69 reference statements)
3
76
3
Order By: Relevance
“…Similarly, the loss of the S-box riboswitch regulating methionine biosynthesis in the Lactobacillales has lead to the expansion of MET-T-boxes in the Lactobacillaceae lineage (whereas in the Streptococcus spp. these genes are regulated by a new transcription factor, MtaR/MetR) Kovaleva and Gelfand 2007;Sperandio et al 2007).…”
Section: Duplications and Expansion Of T-box Regulonsmentioning
confidence: 99%
“…Similarly, the loss of the S-box riboswitch regulating methionine biosynthesis in the Lactobacillales has lead to the expansion of MET-T-boxes in the Lactobacillaceae lineage (whereas in the Streptococcus spp. these genes are regulated by a new transcription factor, MtaR/MetR) Kovaleva and Gelfand 2007;Sperandio et al 2007).…”
Section: Duplications and Expansion Of T-box Regulonsmentioning
confidence: 99%
“…The conservation of LTTRs within the genomes of extremely diverse bacteria means that they have evolved a regulatory role over genes with similarly diverse functions, whose products can be involved in metabolism, cell division, quorum sensing, virulence, motility, nitrogen fixation, oxidative stress responses, toxin production, attachment and secretion, to name a few (Table 1) (Kovacikova & Skorupski, 1999;Deghmane et al, 2000Deghmane et al, , 2002Cao et al, 2001;Kim et al, 2004;Russell et al, 2004;Byrne et al, 2007;Lu et al, 2007;Sperandio et al, 2007). This review aims to bring together the increasing body of knowledge concerning the structure, functions and molecular genetics that is helping to unravel the paradigm of the largest group of transcriptional regulators identified within the prokaryotic kingdom.…”
Section: Introductionmentioning
confidence: 99%
“…identified as being important regulators of the genes related to cysteine and methionine metabolism in streptococci (25,68,69). They belong to the LysR family of transcription regulators.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Hullo et al (30) reported on the regulatory mechanisms related to cysteine and methionine conversions in Bacillus subtilis. Sperandio et al described these relations for Lactococcus lactis (70) and Streptococcus mutans (68,69). Rodionov et al (59) and Kovaleva and Gelfand (36) performed a comprehensive comparative in silico study for the…”
mentioning
confidence: 99%
See 1 more Smart Citation